Columellar Lengthening on Corrected Cleft Lip and Palate (La—aL) Post Cheilorrhaphy: A Case Report - Zeeva, Evane Jovanie; Norholila; Santoso, Clara Cindy Ateng; Effendi, Muchiddin Andri Setyo; Medina, Nadra Odifa; Adiwinoto, Ronald Pratama; Prameswari, Renata (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2025)
Introduction: The Cleft Lip and Palate (CLP) is a congenital malformation involving the orofacial region. The failure of frontonasal and maxillary processes to fuse causes a gap through the lips, alveoli, base of the nose, and in the hard and/or soft palate. Case Presentation: This case report illustrates a 2-year-3-month-old female patient diagnosed with bilateral cleft lip and palate at birth. The patient underwent cheilorrhaphy at 4 months old and currently plans to have scar revision and columellar lengthening surgery at Dr. Ramelan Naval Hospital, Surabaya. The patient presents with a flat nose, a hypertrophic scar above the lip, and speech articulation impairment. Her medical history includes prenatal maternal hypertension, neonatal pneumonia, and exposure to cigar smoke. Additionally, there is a family history of cleft lip and palate. This case highlights the vital role of columellar lengthening in enhancing nasal appearance and airway patency for optimal outcomes without complications. Conclusion: Cleft lip and palate (CLP) require multidisciplinary care. Columellar lengthening and scar revision have been proven effective in enhancing nasal functions and aesthetics. The presence of prenatal maternal hypertension, exposure to cigar smoke, and familial history of CLP accentuates etiological complexity. The case shows successful intervention balancing function, aesthetics, and craniofacial growth in CLP repair. This study aims to increase insight for future management concerning nasal deformities in CLP patients.